A baadasssss song: the wah pedal, a porn meme, and the Blaxploitation sonotope. Issue 1 (2nd January 2023) - Wilder, S. A.
ABSTRACT: In the 1990s, a shorthand for hardcore pornography proliferated in American popular discourse. This sonic signifier tends to be spoken or written as 'bow-chicka-bow-wow'. The phrase's likely source is the wah pedal. Embraced by guitarists in the late 1960s, the wah pedal proved influential to the then-emerging funk genre. That wah-influenced phrase persists as a porn descriptor due to the intersection of the introduction of hardcore pornographic films and the roughly contemporaneous arrival of Blaxploitation in urban grindhouses. Blaxploitation produces a sonotope, a chronotope whereby sound constitutes part of the constellation of genre elements with a fused relationship to a specific time and place. Blaxploitation films become synonymous with urban vice at the same time once illicit pornographic films are being publicly screened for audiences. With the widescale adoption of the amplifying circuit of home video technology, the result is a problematic conflation of Blaxploitation and pornography in the cultural imaginary.